MADRASAH DAN MASALAH IATI DIRT PENDIDIKAN ISLAM - Suprayogo, Imam (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2005)
According to 'Undang-Undang Sisdiknas' no. 2Q of the year 2003, both the position and the status of Madrasah are on a par with the public school. Most people, however, still regard Madrasah as "second class" when seen from such aspects as: graduate prospects, school facilities; school buildings, students' as well as teachers' performances, management of the school, and cooperation with other institutions and stakeholders. Muslim society and the government, in this case, the Department of Religious Affairs, have come to realize these unfavorable situations, so that some efforts have been made to build a better condition of Madrasah. The Department ofReligious Affairs has been trying to improve Madrasah by developing some strategies through the establishment of Madrasah Unggulan (Khusus), Madrasah Terpadu, Madrasah Tsanawiyah Terbuka, Madrasah Aliyah Program Keterampilan, and Madrasah Aliyah Keagamaan (MAK). The questions are: Will Madrasah be a progressive, modern, and reliable Islamic institution? Meanwhile, in the Muslim society, the current image is that Madrasah is an educational institution that has Islamic, Muslim and Islamic educational identities. Will the change imposed on Madrasah institution have some impact on its identity? This article is an attempt to answer these questions.